Prevalence and impact of fertility preservation among young women with breast cancer - Min Chen; Xuan Wang; Ning Lan; YanKe Chen; Ying Gao; Junyang Wang; WenJuan Wang; Min Jiao; Shuheng Bai; Wenyang Li; Fang Wu; Fengyuan Hu; et al. (Scientific Reports)
Abstract To observe the current situation of fertility preservation among female breast cancer patients ≤ 40 years old and analyze the related factors which influence the utilization of fertility preservation. A single-center retrospective questionnaire was conducted investigating patients diagnosed with breast cancer attending The First Affiliated Hospital of Xian JiaoTong University between January 2016 and December 2019. The questionnaire was redesigned based on previous similar research and the questions needed in this study. Rates of utilization of preservation services were compared based on patients’ demographic and economic-social information, disease characteristic information and fertility related information. Univariate and multivariate logistic regression analysis was used to assess the relationship between utilization of fertility preservation and sociodemographic factors, previous reproductive-related problems. 313 patients were successfully interviewed. 60/313patients (19.2%) had utilized fertility preservation. Younger patients (< 30 years of age), patients with 1 or no child, and patients had higher education level were more likely to pursue fertility preservation than their matched counterparts. Age, parity, and education level of breast cancer patients may impact rates of fertility preservation among reproductive age women diagnosed with breast cancer. Thus, further attention to age difference and patient’s desire for future fertility could help to improve gaps in fertility preservation. These findings have guidance for counseling young breast cancer patients.